2019
DOI: 10.1111/jgh.14789
|View full text |Cite
|
Sign up to set email alerts
|

No association between proton pump inhibitor use and risk of dementia: Evidence from a meta‐analysis

Abstract: Background and AimA growing body of literature suggests the association between dementia risk and proton pump inhibitor (PPI) use. Therefore, we aimed to investigate the association between PPI use and dementia risk.MethodsAn extensive literature search was performed in PubMed, Embase, and Cochrane till March 31, 2019. All the studies (cohort and case–control) assessing the association between PPI use and dementia risk were eligible for inclusion. Articles were selected based on the screening of title and abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 65 publications
1
24
0
1
Order By: Relevance
“…For the factor follow-up time ≥ 5 years, the pooled HR was 1.28 (95% CI 1.12-1.46), demonstrating a 1.28-fold increase in the risk of dementia among PPIs users 29 . However, other studies did not found this increased risk of dementia (RR 1.23; 95% CI 0.90-1.67), (RR 1.05; 95% CI 0.96-1.15) and (HR 1.10; 95 CI 0.88-1.37), respectively [28][29][30] . This risk was also not observed when we specifically assessed the risk of AD RR 1.01 (95% CI 0.78-1.32) and HR 1.06 (95% CI 0.72-1.55) respectively 27,30 .…”
Section: Discussionmentioning
confidence: 98%
“…For the factor follow-up time ≥ 5 years, the pooled HR was 1.28 (95% CI 1.12-1.46), demonstrating a 1.28-fold increase in the risk of dementia among PPIs users 29 . However, other studies did not found this increased risk of dementia (RR 1.23; 95% CI 0.90-1.67), (RR 1.05; 95% CI 0.96-1.15) and (HR 1.10; 95 CI 0.88-1.37), respectively [28][29][30] . This risk was also not observed when we specifically assessed the risk of AD RR 1.01 (95% CI 0.78-1.32) and HR 1.06 (95% CI 0.72-1.55) respectively 27,30 .…”
Section: Discussionmentioning
confidence: 98%
“…Omeprazole and other PPIs have come under increased scrutiny because they are pervasively prescribed and used, frequently at doses that are higher than required to inhibit acid secretion and for longer periods than are clinically indicated [10][11][12][13]. Furthermore, a series of investigations has linked PPI use to a number of conditions that include cardiovascular disease [14], osteoporosis [15], C. Difficile colitis [16], community acquired pneumonia [17], and dementia [18][19][20], though different groups have arrived at opposite conclusions [21,22]. The causal effect on these conditions has been debated, though a recent randomized control study suggested that only enteral infections were increased by pantoprazole administration within a three year follow-up period [23].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no consensus on the association between the use of PPIs and the risk of dementia [5][6][7]. Inconsistencies between observational studies, especially those based on claims data, have contributed to the doubtfulness of their utility in clinical decision-making [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistencies between observational studies, especially those based on claims data, have contributed to the doubtfulness of their utility in clinical decision-making [38,39]. Specifically, summary effect estimates of several recent meta-analyses suggested no effect of PPI use on dementia risk [5,6,40,41]. On the other hand, plausible pathophysiological pathways of brain deterioration that PPIs might be involved in such as increased amyloid-β plaques, increased tau protein formation, and vitamin B12 deficiency have been described and need to be taken into account when evaluating the available evidence [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation